State-Owned Enterprise Partnership Program as a Form of Corporate Social Responsibility to Small and Medium Enterprises - Muhammad Yusrizal (Randwick International of Social Science Journal, 2021)
State-Owned Enterprises (SOEs) have a very important role in the implementation of the national economy in order to realize the welfare of the people. SOEs are seen as having a strategic role in fostering and developing private and cooperative businesses. The government through its regulations has mandated SOEs to participate in assisting the government in implementing the development policies that have been outlined, this is as mandated in Article 88 of Law no. 19 Year 2003 on SOEs, which in the article instructs SOEs to set aside a parcel of their net benefit for the reason of cultivating little businesses and cooperatives as well as cultivating the community around the company. The existence of the provisions of Article 88 means that SOEs are not only looking for profit, but also must play an active role in developing and fostering small businesses and cooperatives, so SOEs will have the responsibility Corporate social responsibility that can be sued is the same as other private companies in Indonesia.